Treatment of hepatitis C virus infection in patients with cirrhosis and predictive value of model for end‐stage liver disease: Analysis of data from the Hepa‐C registry. Issue 6 (28th April 2017) - Fernández Carrillo, Carlos; Lens, Sabela; Llop, Elba; Pascasio, Juan Manuel; Crespo, Javier; Arenas, Juan; Fernández, Inmaculada; Baliellas, Carme; Carrión, José Antonio; de la Mata, Manuel; Buti, Maria; Castells, Lluís; et al.
Abstract : Direct‐acting antiviral agents (DAAs) are highly effective and well tolerated in patients with chronic hepatitis C virus infection, including those with compensated cirrhosis. However, fewer data are available in patients with more advanced liver disease. Our retrospective, noninterventional, national, multicenter study in patients from the Spanish Hepa‐C registry investigated the effectiveness and safety of interferon‐free DAA regimens in patients with advanced liver disease, including those with decompensated cirrhosis, in routine practice (all currently approved regimens were registered). Patients transplanted during treatment or within 12 weeks of completing treatment were excluded. Among 843 patients with cirrhosis (Child‐Turcotte‐Pugh [CTP] class A, n = 564; CTP class B/C, n = 175), 90% achieved sustained virologic response 12 weeks after treatment (SVR12). Significant differences in SVR12 and relapse rates were observed between CTP class A and CTP class B/C patients (94% versus 78%, and 4% versus 14%, respectively; both P < 0.001). Serious adverse events (SAEs) were more common in CTP class B/C versus CTP class A patients (50% versus 12%, respectively; P < 0.001). Incident decompensation was the most common serious adverse event (7% overall). Death rate during the study period was 16/843 (2%), significantly higher among CTP class B/C versus CTP class A patients (6.4% versus 0.9%; P < 0.001). Baseline Model for End‐Stage Liver Disease (MELD) score alone (cut‐off 18) was the best predictor of survival. Conclusion : Patients with decompensated cirrhosis receiving DAAs present lower response rates and experience more SAEs. In this setting, a MELD score ≥18 may help clinicians to identify those patients with a higher risk of complications and to individualize treatment decisions. (Hepatology 2017;65:1810‐1822).